The citizen and the state : criminal justice and civil liberties in conflict - Nurse, Angus (Emerald Publishing Limited, 2020)
The Citizen and the State conducts an essential criminological analysis of contemporary justice systems, combining critical criminology and human rights perspectives. The book contextualizes criminal justice and criminal justice processes as tools of the state that impact negatively on citizens' lives. Particularly in a post 9/11 world where 'national security' and terrorism concerns are used as justification for the erosion of citizens' rights, justice systems are inherently in conflict with principles of liberty and justice enshrined in human rights instruments. While acknowledging the reality of changes in law-and-order discourse, this book argues that contemporary justice systems risk lacking in legitimacy in circumstances where the necessity for interference in rights is largely asserted rather than demonstrated. Using a range of real-world case studies, the book conducts a critical analysis of contemporary criminal justice and examines the challenges in achieving a balance between effective criminal justice and upholding civil liberties. This book is essential reading for academics, post-graduate researchers, and social policy professionals.